2019
DOI: 10.3389/fcimb.2019.00160
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Alternative Lipooligosaccharide Glycosyltransferase Activity by UDP-Galactose Epimerase Enhances Murine Lung Infection and Evasion of Serum IgM

Abstract: In pathogens that produce lipooligosaccharide (LOS), sugar residues within the surface-exposed LOS outer core mediate interactions with components of the host immune system, promoting bacterial infection. Many LOS structures are controlled by phase variation mediated by random slipped-strand base mispairing, which can reversibly switch gene expression on or off. Phase variation diversifies the LOS, however its adaptive role is not well-understood. Nontypeable Haemophilus influenzae (NTHi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Here, we showed that production and secretion of IcsA were not affected in the SfpgdA and Sfgtr4 mutants ( Figure 3 A), suggesting the existence of additional mechanisms involved in biofilm formation by Shigella . More recent study reported that the biofilm formation by Gram-negative Haemophilus influenzae was increased by deletion of galE gene and the remarkable availability of UDP-GlcNAc precursors [ 38 ]. The same study reported that the suppression of alternative lipooligosaccharides glycosyltransferase activity by UDP-Galactose epimerase enhanced murine lung infection and evasion of serum IgM [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we showed that production and secretion of IcsA were not affected in the SfpgdA and Sfgtr4 mutants ( Figure 3 A), suggesting the existence of additional mechanisms involved in biofilm formation by Shigella . More recent study reported that the biofilm formation by Gram-negative Haemophilus influenzae was increased by deletion of galE gene and the remarkable availability of UDP-GlcNAc precursors [ 38 ]. The same study reported that the suppression of alternative lipooligosaccharides glycosyltransferase activity by UDP-Galactose epimerase enhanced murine lung infection and evasion of serum IgM [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…One might consider that the ability of WT Shigella to modify its surface, by targeting either PG and/or LPS, is to subvert bacterial detection by the host immune system. Neutrophil-phagocytosed Shigella are killed rapidly by different mechanisms including proteolytic enzymes, antimicrobial proteins, and reactive oxygen species [ 38 ]. Thus, further investigations are needed to unravel mechanisms underpinning Shigella ’s circumvention and/or counteraction of the host’s immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we investigated antibody-dependent complement activity and identified structures on the surface of H. influenzae that are targets for binding and subsequent killing by serum antibodies and complement. Antibody and the classical pathway of complement are required for the bactericidal effect of normal human serum on NTHi (21,26,27). The majority of naturally occurring antibody directing the complement-mediated killing of NTHi is specific to the LOS, and anti-LOS IgM titers correlate with increased serum bactericidal activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…While IgG antibodies against NTHi are present in most individuals, the majority of individuals lack abundant IgM against the LOS of wild-type (WT) NTHi (25). Nevertheless, bactericidal natural or naturally acquired serum IgM against NTHi mutants with truncated LOS structures has been detected (21,26), and these antibodies may recognize NTHi expressing LOS structures modified by phase variation or in response to environmental signals encountered during infection.…”
mentioning
confidence: 99%
“…Microevolution in experimental settings [60] , [61] B. Genome-wide genetic screening B1. HITS* based in vivo genetic screenings [12] , [67] , [68] B2. Tn-seq based in vitro genetic screenings [69] , [70] , [71] , [72] , [73] C. Genome-wide gene expression profiling C1.…”
Section: Introductionmentioning
confidence: 99%